2019
DOI: 10.1108/jed-07-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Productivity growth and job reallocation in the Vietnamese manufacturing sector

Abstract: Purpose The purpose of this paper is to measure TFP growth and job reallocation in the Vietnamese manufacturing industry after the Doimoi period. Design/methodology/approach The study uses firm-level panel data from Vietnam’s annual enterprise survey data for 2000–2016 period in the Vietnamese manufacturing industry using Olley–Pakes static and dynamic productivity decomposition methods. Findings The aggregate productivity estimated from the WRDG method increased 2.323 percent, of which over 40 percent is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Each transition period according to a time difference of about 15 years will group into a generation with different personality characteristics and perceptions. Each generation group will have significant differences and differences in thinking and lifestyle (Nguyen et al, 2019). Presently, in the 20s of the 21st century, it is been accepting young citizens of Gen Z. Nguyen (2020), Bach et al (2022) showed that generation is a diverse, hyper-connected, short-lived group of influencers who are the business force across industries, brands, and digital platforms.…”
Section: Mobile Banking Trendmentioning
confidence: 99%
“…Each transition period according to a time difference of about 15 years will group into a generation with different personality characteristics and perceptions. Each generation group will have significant differences and differences in thinking and lifestyle (Nguyen et al, 2019). Presently, in the 20s of the 21st century, it is been accepting young citizens of Gen Z. Nguyen (2020), Bach et al (2022) showed that generation is a diverse, hyper-connected, short-lived group of influencers who are the business force across industries, brands, and digital platforms.…”
Section: Mobile Banking Trendmentioning
confidence: 99%
“…Labour productivity has been of researchers' interest, especially in the context of developing countries like Vietnam, where the labor market is usually intensive (Ho, 2014;Ha et al, 2019;Minh et al, 2019;Nguyet, 2011;Tran and La, 2018;Vinh, 2019). According to the neoclassical growth model introduced by Solow (1957), labor productivity is driven by total factor productivity (TFP) and capital deepening, which has been acknowledged as one of the key determinants of economic growth in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author documented several important findings, including capital intensity of Vietnam's agricultural sector, a higher productivity level of provinces in South Vietnam, the importance of labor mobility in resources accumulation in agriculture and TFP growth; and the factors affecting agricultural TFP (including land quality, farm size, and land fragmentation). Minh et al (2019) used Olley-Pakes static and dynamic productivity decomposition methods to measure TFP growth and job reallocation in the Vietnamese manufacturing industry after the 1986 political-socio-economic reform Doi Moi. The authors indicated two main reasons for TFP growth, including the within-firm productivity and net entry components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have highlighted the important role of formality and investments in firm growth and national economic development (Monteiro and Assunção, 2006;Nguyen et al, 2018a;Nguyen and Dong, 2013;Rand and Torm, 2012). Both formality and investments contribute to enhancing the capacity and competitiveness of firms, which may result in a higher level of performance and growth (Minh et al, 2019;Nguyen et al, 2016a;Nguyet, 2011;Rand and Torm, 2012). Formally registered firms are more likely to perform better with regard to higher profits and investments (McKenzie and Sakho, 2010;Rand and Torm, 2012).…”
Section: Introductionmentioning
confidence: 99%